Evaluasi Kualitas Tanah di Lahan Sawah Simantri dan Non Simantri di Subak Riang Desa Riang Gede, Kecamatan Penebel - NI LUH AYU PADMAWATI; I DEWA MADE ARTHAGAMA; KETUT DHARMA SUSILA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
Soil Quality Evaluation of Paddy Soil Under “Simantri’s” and Non “Simantri’s” System in Subak Riang, Riang Gede Village, Penebel Subdistrict This experiment conducted to evaluate the differences between soil quality of paddy soil sunder “Simantri’s” and “non Simantri’s” activities, as well as to evaluate the differences among major physical, chemical and biological soil properties which determining their quality. There were three steps applied in this study including: field survey to determine the research area and sampling points; Minimum Data Set to determine the soil quality and t-test to determine the dominant factor which influencing the soil quality. The results of this study showed: the soil quality of faddy soil under “Simantri’s”activity is better than“non Simantri’s” conditions. Other Than That, it was found the soil total nitrogen significantly higher under “Simantri’s” than “non Simantri’s” conditions.